2017
DOI: 10.5267/j.esm.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Large plasticity induced crack initiation from U-notches in thin aluminum sheets under mixed mode loadin

Abstract: Ductile failure is investigated experimentally and theoretically in U-notched Al 7075-T6 thin sheets under mixed mode I/II loading. First, several U-notched rectangular sheets are subjected to mixed mode I/II failure tests and the load-carrying capacity of the sheets are experimentally recorded. Then, the Equivalent Material Concept (EMC) is employed in conjunction with the U-notch maximum tangential stress (UMTS) and U-notch mean stress (UMS) criteria to theoretically estimate the load-carrying capacity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 52 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…aluminum alloys in aerial vehicles etc. Recently, some research works have been performed on ductile failure of notches under various loading conditions [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…aluminum alloys in aerial vehicles etc. Recently, some research works have been performed on ductile failure of notches under various loading conditions [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…To check whether EMC is capable of being combined with brittle fracture criteria in the context of the linear-elastic notch fracture mechanics (LENFM) for predicting failure in engineering components made of ductile materials other than the steel materials reported in Refs. [6,10], some new ductile failure analyses have been recently carried out by Torabi and co-researchers [11][12][13][14][15][16][17] on notched aluminum plates under different in-plane loading conditions. They have published seven papers on this subject; three on pure mode I loading [11,13,15] and four on mixed mode I/II loading [12,14,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They demonstrated that a linear elastic analysis allows to summarize all the high phases of the given cycle of fatigue resistance using a single SED value. Torabi's other works with Mohammad Hosseini [12] have experimentally and theoretically studied U-slotted Al 7075-T6 plates under the mixed loading mode (I / II). The concept of equivalent material (EMC) is used in conjunction with the criterion of maximum tangential stress (UMTS) and mean stress UMS.…”
Section: Introductionmentioning
confidence: 99%